O varstvu Blagayevega volčina na Slovenskem - Strgar, Vinko (Varstvo narave, 1975)
The selling of the Daphne blagayana Freyer in the markets has been put off by law for the protection of rare plants. But the destruction in the habitats still continues. As the branclets of this plant are very tough, the "day-trippers" cannot break them off easily and they pull the plants out together with their roots. This dangerous could be avoided by cultivating this plant for sale.
Keywords: Blagayev volčin; Daphne blagayana; fitogeografija; ogrožene vrste; Slovenija; varstvo narave